Extração e Doseamento da Cafeína em Bebidas Energéticas: A bebida TOP entre os adolescentes! - Galacho, Cristina (2021)
ABSTRACT Extraction and determination of caffeine in energy drinks. One of the most popular drinks among teenagers! With the worldwide consumption of energy drinks increasing in recent years and documented in several international and national studies, it is crucial to increase the awareness of society, in general, and of young people, in particular, for this type of consumption and for the potential risks! This article presents a practical laboratory work that aims the extraction and determination of caffeine contents in energy drinks. The main techniques used are liquid-liquid extraction (single and multiple) and ultraviolet-visible spectrophotometry. Relevant safety aspects, relating to the solvent, are also taken into account, namely, the analysis of Physical, Health and Environmental Hazards, Hazard statements, Precautionary statements, as well as personal protective equipment, PPE, and collective protective equipment, CPE, based on the safety data sheets, SDS. RESUMO Perante o crescente e elevado consumo de bebidas energéticas, verificado nos últimos anos a nível mundial e documentado em diversos estudos internacionais e nacionais, é fundamental aumentar a consciencialização da sociedade, em geral, e dos jovens, em particular, para este tipo de consumo e para os seus potenciais riscos! Neste artigo é apresentado um trabalho prático laboratorial que visa a extração e doseamento da cafeína de bebidas energéticas. Como técnicas principais são usadas a extração líquido-líquido (simples e múltipla) e espectrofotometria de ultravioleta-visível. Os aspetos relevantes de segurança, relativos ao solvente, são igualmente tidos em consideração, nomeadamente, a análise dos Perigos Físicos, para a Saúde e para o Ambiente, das Advertências de Perigo e Recomendações de Prudência, e ainda dos equipamentos de proteção pessoal, EPI, e coletiva, EPC, baseada nas fichas de dados de segurança, FDS.